Over-the-Scope Clip in the Treatment of Gastrointestinal Leaks and Perforations - Mike T. Wei; Ji Yong Ahn; Shai Friedland (Korean Society of Gastrointestinal Endoscopy, 2021)
While perforations, postoperative fistulas, and leaks have traditionally led to surgical or interventional radiology consultation for management, the introduction of the over-the-scope clip has allowed increased therapeutic possibilities for endoscopists. While primarily limited to case reports and series, the over-the-scope clip successfully manages gastrointestinal bleeding, perforations, as well as postoperative leaks and fistulas. Retrospective studies have demonstrated a relatively high success rate and a low complication rate. Given the similarity to variceal banding equipment, the learning curve with the over-the-scope clip is rapid. However, given the higher risk of procedures involving the use of the over-the-scope clip, it is essential to obtain the scope in a stable position and grasp sufficient tissue with the cap using a grasping tool and/or suction. From our experience, while closure may be successful in lesions sized up to 3 cm, successful outcomes are obtained for lesions sized <1 cm. Ultimately, given the limited available data, prospective randomized trials are needed to better evaluate the utility of the over-the-scope clip in various clinical scenarios, including fistula and perforation management.